Additive manufactured cerium oxide foils, used as pads for polishing processes of brittle-hard materials - Schulze Christian; Henkel Sebastian; Schultheiß Denise; Pipiorka Dominique; Bliedtner Jens; Kerber Albert; Rädlein Edda (EPJ Web of Conferences)
A new concept for polishing pads for flat and spherical surfaces is introduced which comprises additive manufactured polishing pads made of cerium oxide. By using additive manufacturing technologies, polishing processes with polishing slurry can be substituted with tools containing bonded grain. The bonded polishing pads can be fabricated using rolling processes. The pad geometries can be adjusted by using laser cutting. Furthermore, surface modifications of the pad can be applied with laser processes to favour quality and economic factors of the polishing procedure. First results from the experimental setup are showing, that lapped surfaces with a roughness Rq of ~ 500 nm can be improved to approx. Rq = 30 nm roughness by polishing with bonded grain cerium oxide foils. Further approaches for future investigations and applications are proposed.